Analysis Of Supervision of The Use of PPE On Workers in Company Sinar Alam Duta Perdana - Norsita Agustina; Meilya Farika Indah; Asrinawaty Asrinawaty; Chandra Chandra; Eka Handayani (Lambung Mangkurat University, 2025)
Occupational Health and Safety (K3) is our effort to create a healthy and safe work environment, so that it can reduce the probability of work accidents / diseases due to negligence that result in demotivation and deficiencies in work productivity. This study aims to determine the supervision of the use of PPE in workers at PT. Sinar Alam Duta Perdana II in 2024. This type of research uses a quantitative research method. The sampling technique uses a purposive sampling technique based on characteristics, namely field workers with a sample size of 40 people using a questionnaire measuring instrument, data analysis using the chi square test, the results of the statistical test show that there is a relationship between supervision (p-value = 0.034) and no relationship between training (p-value = 0.059) with compliance with the use of PPE at PT. Sinar Alam Duta Perdana II in 2024, There is no relationship between motivation (p-value = 0.0721) with compliance with the use of PPE at PT. Sinar Alam Duta Perdana II in 2024. For the Company, it is recommended to increase supervision of the use of PPE by workers.